Influence of cervical, thoracic and lumbar spines, and shoulder girdle range of motion on swallowing function of dependent older adults. Issue 12 (28th June 2017) - Tashiro, Munetsugu; Honda, Yasutoshi; Ohkubo, Mai; Sugiyama, Tetsuya; Ishida, Ryo
Abstract: Aim: The present study examined the cervical, thoracic and lumbar spines, and shoulder girdle range of motion (ROM) of dependent older adults to clarify the influence of these variables on swallowing function, in order to evaluate the efficiency of ROM training to maintain older adults' swallowing function. Methods: A total of 37 (mean age 86.8 ± 6.2 years; 11 men; 26 women) dependent older adults were included in the study. The level of swallowing function was assessed using the Functional Oral Intake Scale. The following ROM were measured three times to calculate the mean: the cervical spine (flexion, extension, rotation and lateral bending); thoracic and lumbar spines (flexion, extension, rotation and lateral bending); and shoulder girdle (flexion, extension, elevation and depression). In order to compare ROM, the participants showing Functional Oral Intake Scale scores of 7 were classified as dysphagia (−), and those showing scores <7 were included in the dysphagia (+) subgroups. Results: The dysphagia (+) group showed significantly limited cervical spine (flexion, extension and lateral bending), thoracic and lumbar spines (flexion, extension, rotation and lateral bending), and shoulder girdle (flexion, elevation, and depression) ROM. Conclusions: Although strict relationships were not clarified, the results of the present study suggested the influence of some joint ROM on swallowing function. This suggests the feasibility of preventing dysphagia among dependent older adults by maintaining and enhancing the elasticity and extensibility of their muscles through cervical, thoracic and lumbar spines, and shoulder girdle ROM training.Geriatr Gerontol Int 2017; 17: 2565–2572 .